Dynamics of legal regulation of educational rights - V. Gribanov, Ph. D. Dmitry; Kovalenko, Ph. D. Kseniya (Revista Conrado, 2017)
The article analyzes the regulatory legal regulation of educational legal relations of Russia from the late XX to the beginning of the 21st century. The authors analyzed the history of the national legislation on education and the dynamics of its development. Three stages of development of the educational legislation are defined and the features of each stage are grounded. Educational legal relations are a special kind of social relations that arise on the basis of the norms of the educational law of the students (or their legal representatives), educational institution and teachers in connection with the organization, management and implementation of educational activities (educational process). Other educational legal relations - conditioned by the educational law and serving educational legal relations, developing on the basis of norms of administrative, civil, labor, financial and other branches of law. Other educational relations provide the process and result of educational activities, the functioning of the entire education system, according to its goals and objectives. Keywords: Educational legal relations, vocational education, higher education, law, legal regulation. RESUMEN El artículo analiza la regulación legal de regulación de las relaciones jurídicas educativos de la Rusia de finales del XX a principios del siglo 21. Los autores analizaron la historia de la legislación nacional sobre la educación y la dinámica de su desarrollo. Tres etapas de desarrollo de la legislación educativa se definen y se ponen a tierra las características de cada etapa. Las relaciones jurídicas educativas son un tipo especial de relaciones sociales que surgen sobre la base de las normas de la ley educativa de los estudiantes (o de sus representantes legales), de la institución educativa y de los docentes en relación con la organización, gestión y ejecución de actividades educativas Proceso). Otras relaciones jurídicas educativas - condicionadas por la ley educativa y que sirven a las relaciones jurídicas educativas, desarrollándose sobre la base de normas de derecho administrativo, civil, laboral, financiero y otras ramas del derecho. Otras relaciones educativas proporcionan el proceso y resultado de las actividades educativas, el funcionamiento de todo el sistema educativo, de acuerdo con sus objetivos y metas. Palabras clave: Las relaciones jurídicas de educación, formación profesional, educación superior, el derecho, la regulación legal.